T-Cell Factors as Transcriptional Inhibitors: Activities and Regulations in Vertebrate Head Development - Bou-Rouphael, Johnny; Durand, Béatrice C. (Frontiers in Cell and Developmental Biology, 2021)
Since its first discovery in the late 90s, Wnt canonical signaling has been demonstrated to affect a large variety of neural developmental processes, including, but not limited to, embryonic axis formation, neural proliferation, fate determination, and maintenance of neural stem cells. For decades, studies have focused on the mechanisms controlling the activity of β-catenin, the sole mediator of Wnt transcriptional response. More recently, the spotlight of research is directed towards the last cascade component, the T-cell factor (TCF)/Lymphoid-Enhancer binding Factor (LEF), and more specifically, the TCF/LEF-mediated switch from transcriptional activation to repression, which in both embryonic blastomeres and mouse embryonic stem cells pushes the balance from pluri/multipotency towards differentiation. It has been long known that Groucho/Transducin-Like Enhancer of split (Gro/TLE) is the main co-repressor partner of TCF/LEF. More recently, other TCF/LEF-interacting partners have been identified, including the pro-neural BarH-Like 2 (BARHL2), which belongs to the evolutionary highly conserved family of homeodomain-containing transcription factors. This review describes the activities and regulatory modes of TCF/LEF as transcriptional repressors, with a specific focus on the functions of Barhl2 in vertebrate brain development. Specific attention is given to the transcriptional events leading to formation of the Organizer, as well as the roles and regulations of Wnt/β-catenin pathway in growth of the caudal forebrain. We present TCF/LEF activities in both embryonic and neural stem cells and discuss how alterations of this pathway could lead to tumors.